Morphological Variations of Middle Ear Ossicles and its Clinical Implications - Saha, Ritaban (J Clin Diagn Res, 2017)
INTRODUCTION: The middle ear ossicles form a semi rigid chain in the middle of the ear for conduction and amplification of sound waves from the tympanic membrane to the inner ear. Although, our knowledge of the ear ossicles dates back to the 15(th) century, and various studies have been carried out on their morphometry, morphology, anomalies, embryology, function and structure throughout the world, information about the morphology of middle ear ossicles is meagre in Indian subjects. AIM: To find out the morphological variations of middle ear ossicles of right and left sides. MATERIALS AND METHODS: In the present study, the middle ear ossicles were bilaterally dissected out from the temporal bones obtained from 26 cadaveric heads from the Department of Anatomy under a surgical oto-microscope with micro instruments. Morphological variations were studied under the magnification of the operating microscope. Attempt was also made to evaluate the clinical implications related to such variants and compare the results with those observations made in other parts of India and abroad. Age variation was not considered as the ossicles reach their full size at birth. RESULTS: It was observed that the stapes was the most variable and the incus as the most stable ossicle so far as morphological variations are concerned. Malleus presented variations in the free ends of manubrium, lateral process and anterior process. Variation in morphology of stapes did not follow any fixed pattern. CONCLUSION: It is expected that this work may also inspire many others to continue temporal bone dissection with a view to gather more ossicles which might be preserved in ossicular banks by following proper sterilization methods for future use as homografts in ossiculoplasty. These harvested ossicles may be used to replace eroded middle ear ossicles as an alternative to manufactured prosthesis.